Recurrence of urogenital Chlamydia trachomatis infection evaluated by mailed samples obtained at home: 24 weeks' prospective follow up study. Issue 3 (1st June 2000) - Kjær, H O; Dimcevski, G; Hoff, G; Olesen, F; Østergaard, L
Abstract : Objectives: To evaluate the rate of recurrence of genital Chlamydia trachomatis infection after antibiotic therapy in a population of patients drawn from general practice, and to evaluate whether retesting after antibiotic therapy was advisable and, if so, whether it could be based on a strategy involving samples obtained at home and mailed to the laboratory for analysis. Methods: Prospective follow up study of 42 patients with genital C trachomatis infection drawn from general practice. Patients at or above the age of 18, with a positive urogenital swab sample obtained by a general practitioner were invited to participate. Follow up testing was based on LCR testing (LCx, Abbott diagnostics) of first void urinary and vaginal flush samples taken by the patients at home and mailed to the laboratory at weeks 2, 4, 8, 12, and 24 after antibiotic therapy. Results: Cumulated incidence of recurrent infection was calculated to 29% (95% CI: 12%–46%) during the 24 weeks of follow up. Previous or present sexually transmitted diseases other than C trachomatis were significantly associated with recurrence (OR 6.1, p=0.03). 89% of patients tested negative at week 2, and all patients tested negative at some point during the first 4–8 weeks. 84% of the test kits mailed to the patients were returned to the laboratory for analysis. Conclusions: Recurrence of C trachomatis after antibiotic treatment is a substantial problem. Retesting should be carried out, but not sooner than 12–24 weeks after treatment. Requiring patients to take tests at home appears to be a promising method for retesting.